Selenium-containing polysaccharide from Spirulina platensis alleviates Cd-induced toxicity in mice by inhibiting liver inflammation mediated by gut microbiota - Zhou, Ning; Long, Hairong; Yu, Lian; Xia, Xianghua; Zhu, Zhenjun; Liu, Xiaoling (Frontiers in Nutrition, 2022)
Selenium-containing polysaccharide from Spirulina platensis (Se-SPP) has been demonstrated with benefit on inhibiting cadmium-induced injury in mice, but lacking of underlying mechanism. This study aimed to investigate the beneficial effects of Se-SPP on alleviating Cd-induced toxicity in mice by targeting liver inflammatory and gut microbiota. 28-days Se-SPP supplementation in Cd-induced toxic mice significantly mitigated liver pathological damage and inflammation, which was correlated to the upregulation of antioxidant enzymes activity. Furthermore, Se-SPP effectively restored Cd-induced disruption of the intestinal barrier compared to model group, as indicated by the depletion of Muribaculaceae and the enrichment of Ruminococcaceae. Spearman's correlation analysis revealed that the Se-SPP-altered microbes were highly correlated with inflammation-related indexes in Cd-induced toxic mice. Noteworthily, the modulation of Se-SPP on Ruminococcaceae population contributed to the improvement of Cd-induced inflammation-related diseases by downregulating the tumor necrosis factor-α (TNF-α) and interferon-γ (IFN-γ) in liver. These findings suggested that Se-SPP may acted as prebiotics for ameliorating Cd-induced toxicity in mice through inhibiting liver inflammation mediated by gut microbiota, and target-specific microbiota of Cd-induced inflammation-related diseases deserve further attention.